A post-grafting strategy to modify g-C3N4 with aromatic heterocycles for enhanced photocatalytic activity. Issue 36 (23rd August 2016) - Tian, Jianjian; Zhang, Lingxia; Fan, Xiangqian; Zhou, Yajun; Wang, Min; Cheng, Ruolin; Li, Mengli; Kan, Xiaotian; Jin, Xixiong; Liu, Zhenghao; Gao, Yanfeng; Shi, Jianlin
Abstract : A novel and facile post-grafting strategy has been developed to construct aromatic heterocycle-grafted graphitic carbon nitride photocatalysts. Abstract : A novel and facile post-grafting strategy, instead of conventional copolymerization, via a Schiff base chemical reaction between aldehyde and –NH2 groups has been developed to construct aromatic heterocycle-grafted graphitic carbon nitride (g-C3 N4 ) photocatalysts for the first time. The high-resolution N 1s XPS spectrum and the CO2 TPD analysis confirmed the successful introduction of heterocycles and the reduced structural defects (unreacted –NH2 groups during the copolymerization modification of g-C3 N4 ). The post-grafting of aromatic rings into the g-C3 N4 network did not disrupt the original framework of g-C3 N4, but effectively expanded its π-delocalized system, enlarged its surface area and promoted the separation and transfer of photo-excited charge carriers. As a result, the obtained copolymer composites exhibit significantly enhanced visible-light photocatalytic activity for H2 evolution over pristine g-C3 N4 . This strategy is general and can be used to graft large numbers of aromatic rings of different molecular structures onto g-C3 N4 .